Criminal Law Implications of Personal Data Misuse in the Digital Age - Aliman (Universitas Muhammadiyah Palu, 2025)
The rapid advancement of information technology has significantly transformed modern society, particularly in the way personal data is collected, stored, and processed. While the digital era offers convenience and efficiency, it also presents substantial risks, especially concerning the misuse of personal data by irresponsible individuals, corporations, or other entities with access to sensitive information. Such misuse can take the form of identity theft, online fraud, or unauthorized exploitation of data for economic gain without the data owner's consent. These circumstances highlight the urgent need for comprehensive regulations and effective criminal law mechanisms to protect personal data. This article aims to explore the criminal law implications of personal data misuse within the Indonesian context and assess the extent to which current legal instruments address these challenges. The research adopts a normative juridical approach by analyzing Law No. 27 of 2022 on Personal Data Protection (PDP Law), the Indonesian Penal Code (KUHP), and other related legal provisions. Furthermore, the study examines recent cases to illustrate the weaknesses in cyber law enforcement. The findings reveal that although personal data protection regulations exist, significant gaps remain in implementation, inter-agency coordination, and the effectiveness of criminal sanctions.